2021
DOI: 10.3390/rs13245125
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Lake Area Change and Its Relationship with Climate in the Endorheic Basins of the Tibetan Plateau

Abstract: Lakes are sensitive indicators of climate change in the Tibetan Plateau (TP), which have shown high temporal and spatial variability in recent decades. The driving forces for the change are still not entirely clear. This study examined the area change of the lakes greater than 1 km2 in the endorheic basins of the Tibetan Plateau (EBTP) using Landsat images from 1990 to 2019, and analysed the relationships between lake area and local and large-scale climate variables at different geographic scales. The results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 64 publications
1
8
0
Order By: Relevance
“…Furthermore, Wang et al . 68 also indicated that the trends in the lake area (>1 km 2 ) in the endorheic basin of the QTP are consistent with the SLWB derived in this study. This further supports the validity of the data and conclusions presented in our study.…”
Section: Technical Validationsupporting
confidence: 89%
“…Furthermore, Wang et al . 68 also indicated that the trends in the lake area (>1 km 2 ) in the endorheic basin of the QTP are consistent with the SLWB derived in this study. This further supports the validity of the data and conclusions presented in our study.…”
Section: Technical Validationsupporting
confidence: 89%
“…This study posits that factors such as snowfall, rainfall, surface runoff, and groundwater influx compensate for the water deficit caused by sublimation, thereby stabilizing annual lake surface elevations. However, the recent literature suggests a rise in the water level of Nam Co and an expansion of its surface area in recent years, which may influence its salinity and evaporation rate [18,68,69]. While our investigation was constrained to a bidimensional analysis and Owing to the distinctive climatic conditions of the Tibetan Plateau, numerical simulations of its lakes have revealed limitations, especially in modeling the deep lake ice-on phase.…”
Section: Discussionmentioning
confidence: 99%
“…In the study, we calculated P W and E W amount based on annual lake area extracted from Landsat images (see Section 2.2.2). As the area tends to be the maximum water surface area in a year (J. Wang et al., 2021), the overestimation of P W and E W amount may also introduce some bias and uncertainty to inflow calculation. Followed the uncertainty propagation laws, we estimated the uncertainties of R L rate and amount based on the uncertainty estimates of other water balance terms (Equations , and Figure S18 in Supporting Information ).…”
Section: Discussionmentioning
confidence: 99%
“…With little human disturbance, theses lakes are effective sentinels of climate change and sensitive to hydrological change (Adrian et al., 2009; G. Zhang & Duan, 2021). Under recent regional climate warming and wetting, most lakes in the TP has been undergoing dramatic expansion, manifested as the increase in water surface area, water level and lake water volume (Qiao et al., 2019; J. Wang et al., 2021; G. Zhang et al., 2019; G. Zhang et al., 2020). To illustrate the mechanism of such rapid lake expansion, accurate estimation of lake water balance components, such as lake inflow from catchment ( R L ), lake surface precipitation ( P W ) and evaporation ( E W ), are crucial (Ding et al., 2018; Tong et al., 2016; Zhou et al., 2015).…”
Section: Introductionmentioning
confidence: 99%